External environmental factors affecting export performance in the Algerian food industry companies - Latrach, Jamel; Beka, Cherif (Milev Journal of Research and Studies, 2017)
Export performance of the institutions are large affected by variables obstacles marketing environment. This study sought to determine the impact and the possibility to take advantage from the results to raise thevalue of exports for institutions active in the field of food industries which will increase profits, thus supporting the national economy and overcome the obstacles faced by these institutions in the process of export. A study sample of 33 Foundation has been formed, this sample has accounted for 38.82 percent of the total volume of private community study A questionnaire of the subject study has been formed to collect the necessary data in order to make the research design. The latter has been analyzed using statistical methods. The study concluded that external factors (economic environment, political,legal, technology and competitiveness) adversely affect the export performance of these institutions in varying degrees.